Product service system in circular economy: a bibliometric analysis / Jialu Tang … [et al.] - Tang, Jialu; P. Toyong, Natrina Mariane; Shahlal, Norazmi; Zhu, Minghui (Faculty of Art and Design, 2024)
As global attention to sustainable development increases, more and more works of literature emphasise the application of a circular economy-oriented product service system (PSS). The Circular economy aims to achieve economic and environmental sustainability through efficiency of resources and minimisation of waste. Meanwhile, product service systems are an emerging business model with the potential to facilitate product life extension and recycling. However, despite the growth of this field of study, there are relatively few bibliometric analyses of its application in the circular economy. Therefore, this study aims to use the method of bibliometrics, and with the help of VOS viewer visualisation software, to analyse the relevant literature the application of product-service systems under the guidance of circular economy in Scopus database from 2014 to 2023, and to discuss the publication types and trends, source distribution of publications, the most highly cited articles, and research hotspot keywords analysis. This study found that keyword analysis identified four main topic clusters, in which significant hotspots focused on the Internet of Things, Industry 4.0, consumer behaviour, and reverse logistics. Therefore, this study may benefit researchers who wish to understand relevant academic results circular economy-oriented PSS applications.